(untitled) (CAHIERS MAGELLANES-NS, 2024)
With rapid urbanization, street vending emerged as the important element of informal economy worldwide. Vendors on the street offer essential services to urban people while surviving on their own business, limited resources, and labor. Street vendors’ populace on the street is on the rise in contrary to the perception that with the improvised economy the vendors will subside significantly. Research has been done on informal sector focusing on the quality of life of vendors, economic and social engagements, impact on street and road environment, impact on buildings and overall urban quality of the place. However, the impact of informal sector in altering the urban environment through engagement of public spaces such as streets, pedestrian walkways and open spaces is still missing. The presence of informal activities on one hand economically supports urban areas but on the other it leads to traffic congestion, crowded streets and pedestrian walkways and untidy urban spaces which degrades the overall ambience of the place for which it was designed. Subsequently, the accommodation of street vendors on the available public spaces in commercial markets leads to capture of available green spaces thereby leading to reduction in vegetation and loss of natural environment in a densely populated area. The loss of natural environment accompanied by inflating urban population and increased activities in the market due to presence of street vendors contributes to manmade environment thereby increasing the temperature of the area as an impact of Urban Heat Island. Therefore, the aim of this paper is to examine the impact of informal sector in increasing the temperature of the commercial streets due to creation of manmade environment.